Errors In Speaking English Made By Students Ofenglish Department Of Muhammadiyah University Of Surakarta - Fadhila, Hawa; , Prof. Dr. Endang Fauziati, M. Hum; , Dra. Dwi Haryanti, M. Hum (2013)
The researcher writes this research to describe the type of errors in speaking English of English Department of Muhammadiyah University of Surakarta, describe the frequency and the dominant, and explain the sources of error. The type of this research is descriptive qualitative research. The researcher collects micro teaching video from her friends. The researcher makes the transcript of the video as the source of the data. The researcher uses documentation method to select the data. There are 212 data containing of errors. The researcher uses Clark and Clark theory and Dulay, Burt, and Krashen theory to analyze the errors. The researcher divides the errors into three classifications. They are speech error, lexical error, and grammatical error. In speech errors are repetition (27,4%), unretraced (4,3%), retraced (6,6%), filled pause (20,3%), silent pause (9,9%), stutters (1,9%), correction (0,9%), and slip of the tongue (0,5% ). Lexical error is wrong choice of word (0,9%). Grammatical errors are omission of auxiliary in question (6,1%), omission of "to be" (2,4%), addition of "to be"/ verb (7,6%), omission of "do" in negative sentence (0,5%), addition of "do" in question (1,9%), addition of preposition (2,8%), misordering (0,9%), the use of V-O instead of V-ing (0,5%), addition of "to" after auxilary (1,4%), and wrong choice of verb (3,3%). The sources of speech error are cognitive and psychological reason. The sources of lexical and grammatical error are interlingual and intralingual transfer.